2019
DOI: 10.1055/s-0037-1610699
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Alkoxide/Disilane-Mediated Dehalogenative Deuteration

Abstract: Deuterated compounds are of great importance in chemistry and pharmaceuticals. Reductive dehalogenation is one of the most useful methods to incorporate deuterium into molecules. This article briefly discusses the historical development of dehalogenative deuteration reactions that involve transition-metal catalysis, radical halogen abstraction, alkali-metal reductive deuteration, and the recently developed potassium methoxide/hexamethyldisilane-mediated dehalogenation of aryl halides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Deuterodehalogenation of organohalides is a straightforward strategy with which to incorporate deuterium atoms at specific positions. However, the available methods often rely on transition-metal catalysis and suffer from harsh reaction conditions, narrow substrate scope, and the use of toxic and expensive deuterium sources 38 . Achieving a high level of deuterium incorporation is also a challenging task 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Deuterodehalogenation of organohalides is a straightforward strategy with which to incorporate deuterium atoms at specific positions. However, the available methods often rely on transition-metal catalysis and suffer from harsh reaction conditions, narrow substrate scope, and the use of toxic and expensive deuterium sources 38 . Achieving a high level of deuterium incorporation is also a challenging task 39 .…”
Section: Introductionmentioning
confidence: 99%
“…During our studies of a dehalogenative deuteration of aromatic halides, we unexpectedly found that 5-Br- N -tosylindole ( 1d ) was rapidly converted into 5-Br- N -methylindole ( 2d ) upon treatment with potassium methoxide (see Scheme S1 and Scheme d). Two consecutive displacement steps are involved in this transformation, namely, addition of methoxide (with R = Me for example) to the sulfonamide to generate an anionic species ( I ) and methyl 4-methylbenzenesulfonate ( II ) and a subsequent S N 2 substitution reaction between II and I delivering the methylated product 2 .…”
mentioning
confidence: 99%